FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KETUBAN PECAH DINI PADA IBU BERSALIN DI PUSKESMAS GAJAH MADA TAHUN 2014 – 2016 - Madinah (Jurnal Kesehatan Husada Gemilang, 2022)
Premature rupture of membranes is the leading cause of preterm labor with its consequences. The incidence of KPD approaches 10% of all deliveries. In the case of labor <34 weeks, the incidence was about 4%. The dangers of KPD are the possibility of uterine infection and preterm delivery which may increase maternal and infant morbidity and mortality. The purpose of this study is to analyze the magnitude of risk factors associated with premature rupture in maternity mothers at the Gajah Mada Community Health Center from 2014 to 2016. The type of this research is Cross Sectional Descriptive Analytic. Sample was taken by using Total Sampling. The number of samples in this study was 134 people. The data was expanded through medical record. The data was analyzed by using Chi Square test with p<0,05. The results showed that the variables associated with the incidence of premature rupture of membranes were the p-value of age on 0.000 (p<0.05) and OR (6,711) women with a high risk of life having 6.7 times getting the incidence of KPD compared with women with low risk age. The p-value of work on 0.000 (P <0.05) and OR 8.606, working mothers would have 8.6 times experiencing KPD rather than those who do not. The p-value of gemelli pregnancy on 0.001 (P <0.05) and 4.667 mothers with gemelli pregnancy would get 4.6 times receiving KPD rather than those who do not. The variables which are unrelated to the incidence of premature rupture of membranes are parity, anemia, and breech delivery.